An open-source Matlab code package for improved rank-reduction 3D seismic data denoising and reconstruction - Chen, Yangkang; Huang, Weilin; Zhang, Dong; Chen, Wei (Computers & geosciences, 2016)
Simultaneous seismic data denoising and reconstruction is a currently popular research subject in modern reflection seismology. Traditional rank-reduction based 3D seismic data denoising and reconstruction algorithm will cause strong residual noise in the reconstructed data and thus affect the following processing and interpretation tasks. In this paper, we propose an improved rank-reduction method by modifying the truncated singular value decomposition (TSVD) formula used in the traditional method. The proposed approach can help us obtain nearly perfect reconstruction performance even in the case of low signal-to-noise ratio (SNR). The proposed algorithm is tested via one synthetic and field data examples. Considering that seismic data interpolation and denoising source packages are seldom in the public domain, we also provide a program template for the rank-reduction based simultaneous denoising and reconstruction algorithm by providing an open-source Matlab package. •Traditional rank-reduction based algorithm will cause residual noise.•An improved rank reduction method by slightly modifying the TSVD formula.•Synthetic and field data examples show very encouraging results.•An open-source Matlab code package for seismic processing is introduced.